Metamorphic inheritance of Rheic passive margin evolution and its early‐Variscan overprint in the Teplá‐Barrandian Unit, Bohemian Massif. (7th December 2016) - Peřestý, V.; Lexa, O.; Holder, R.; Jeřábek, P.; Racek, M.; Štípská, P.; Schulmann, K.; Hacker, B.
Abstract: Rift‐related regional metamorphism of passive margins is usually difficult to observe on the surface, mainly due to its strong metamorphic overprint during the subsequent orogenic processes that cause its exposure. However, recognition of such a pre‐orogenic evolution is achievable by careful characterization of the polyphase tectono‐metamorphic record of the orogenic upper plate. A multidisciplinary approach, involving metamorphic petrology, P–T modelling, structural geology and in situ U‐Pb monazite geochronology using laser‐ablation split‐stream inductively coupled plasma mass spectrometry, was applied to unravel the polyphase tectono‐metamorphic record of metapelites at the western margin of the Teplá‐Barrandian domain in the Bohemian Massif. The study resulted in discovery of three tectono‐metamorphic events. The oldest event M1 is L P –H T regional metamorphism with a geothermal gradient between 30 and 50 °C km −1, peak temperatures up to 650 °C and of Cambro‐Ordovician age ( c.  485 Ma). The M1 event was followed by M2‐D2, which is characterized by a Barrovian sequence of minerals from biotite to kyanite and a geothermal gradient of 20–25 °C km −1 . D2‐M2 is associated with a vertical fabric S2 and was dated as Devonian ( c.  375 Ma). Finally, the vertical fabric S2 was overprinted by a D3‐M3 event that formed sillimanite to chlorite bearing gently inclined fabric S3 also of Devonian age. The high geothermal gradient of the M1 event can be explained as the result of an extensional, rift‐related tectonic setting. In addition, restoration of the deep architecture and polarity of the extended domain before the Devonian history – together with the supracrustal sedimentary and magmatic record – lead us to propose a model for formation of an Ordovician passive continental margin. The subsequent Devonian evolution is interpreted as horizontal shortening of the passive margin at the beginning of Variscan convergence, followed by detachment‐accommodated exhumation of lower‐crustal rocks. Both Devonian shortening and detachment occurred in the upper plate of a Devonian subduction zone. The tectonic evolution presented in this article modifies previous models of the tectonic history of the western margin of the Teplá‐Barrandian domain, and also put constraints on the evolution of the southern margin of the Rheic ocean from the passive margin formation to the early phases of Variscan orogeny.